Interspecific competition between Nasonia vitripennis (Walker) and Muscidifurax zaraptor Kogan & Legner (Hymenoptera Pteromalidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Groups of puparia of Musca domestica (100-150-200) were exposed for 48 hours to four couples of Nasonia vitripennis and Muscidifurax zaraptor associated in the ratios 4:0; 1:3; 2:2; 3:1; 0:4. Tests were carried out in a conditioned room at 27±1°C, 70±5% r.h. and photoperiod 14:10 (light:dark). N. vitripennis and M. zaraptor caused a mortality of M. domestica higher than 90% when 100 puparia were exposed to four couples of the same species. A significative decrease in M. domestica mortality was observed when the four couples of parasitoids were composed of individuals of the two species associated in the different ratios. The decrease was due to competition between the females of the two species.
Keywords: Musca domestica; parasitoids; offspring